The summer pact [compact disc, unabridged] - Giffin, Emily (Random House Audio, 2024)
Four freshmen arrive at college from completely different worlds: Lainey, a California party girl with a flair for drama; Tyson, a brilliant scholar and law school hopeful from D.C.; Summer, a recruited athlete and perfectionist from the Midwest; and Hannah, a mild-mannered southerner who is content to quietly round out the circle of big personalities. Soon after moving into their shared dorm, they strike up a conversation in a study lounge, and the seeds of friendship are planted. As their college years fly by, their bond intensifies and the four become inseparable. But as graduation nears, their lives are forever changed after a desperate act leads to tragic consequences. Stunned and heartbroken, a pact is made to be there for each other in their time of need, no matter how separated they are by circumstances or distance. Ten years later, Hannah is anticipating what should be one of the happiest moments of her life when everything is suddenly turned upside down. Calling on her closest friends, it soon becomes clear that they are facing their own crossroads. True to their promise, they agree to take a time out from lives headed in wrong directions and embark on a journey of self-discovery, forgiveness, and acceptance.